Stability of α-Alumina photonic structures formed at low temperatures utilizing chromia-seeding - Pasquarelli, Robert M.; Waleczek, Martin; Nielsch, Kornelius; Schneider, Gerold A.; Janssen, Rolf (Ceramic Transactions, 2016)
Emerging applications of ordered, macroporous oxide photonic structures for thermal barrier coatings, structural coloration, and thermophotovoltaics requires the stability of these features at operating temperatures. However, in high-Temperature environments (>1000 °C), these structures can exhibit significant undesired microstructural changes (phase changes, sintering, grain growth, etc.) that result in a loss of the desired properties. An approach for lowering the formation temperature of α-Alumina in such structures was demonstrated by seeding with chromia by secondary infiltration from precursor solutions. Seeds of α-chromia, which formed at 500 °C, successfully lowered the α-Alumina formation temperature from 1200 to 800 °C by heterogeneous nucleation. Upon heating to 1200 °C, these chromia-seeds went into solid-solution with the alumina structure. However, in contrast to unseeded structures, the resulting microstructures were prone to grain growth and loss of photonic properties upon heating at 1400 °C,.
CRIS-Team Scopus Importer:2023-03-20